Improving rootknot nematode management on two soybean genotypes through the application of Bradyrhizobium japonicum, Trichoderma pseudokoningii and Glomus mosseae in full factorial combinations - Oyekanmi, E.O.; Coyne, Danny L.; Fagade, O.E.; Osonubi, O. (Elsevier, 2007)
The effects of soybean inoculation with arbuscular mycorrhiza fungus Glomus mosseae (200 sporesplant), the nodulating bacterium Bradyrhizobium japonicum (106 cellsplant) and the nematode antagonistic fungus Trichoderma pseudokoningii (6.8×107 sporesplant) were studied. Application of the microorganisms separately, in dual, or in triple combinations were assessed in the presence of the plant-parasitic nematode, Meloidogyne incognita under screen house (1000 second stage juvenileplant) and field (1500 eggsplant) conditions, with two soybean genotypes. The microorganism treatments were compared with application of a synthetic nematicide (Furadan 3G® [a.i. carbofuran]), an untreated control without nematodes and a nematode-only control. Application of the microorganisms in full factorial combinations suppressed nematode reproduction in most cases and reduced nematode galling comparable to the nematicide treatment. The results provide evidence of the potential of beneficial microorganisms in providing equal or better protection against root-knot nematode damage, than the synthetic nematicide carbofuran.